Exploring the Dimensions of Religious Tourist Satisfaction at Gua Maria Ambarawa: A Phenomenological Investigation - Setiamani Buulolo; Pranoto (Jurnal Penelitian, 2025)
This phenomenological study explores the lived experiences and meaning-making processes of religious tourists visiting Gua Maria Ambarawa, investigating how spiritual service quality, worship facilities, accessibility, and religious atmosphere contribute to visitor satisfaction. Employing an interpretive qualitative approach, this research engaged 100 purposively selected participants through in-depth phenomenological interviews, participant observation, and hermeneutic analysis of tourist narratives. Four primary experiential dimensions emerged: spiritual service as divine mediation (prayer services, spiritual guidance, religious information, ritual ceremonies, worship timing); sacred infrastructure as embodied faith (worship capacity, cleanliness as spiritual purity, liturgical equipment, contemplative spaces, supporting facilities); accessibility as pilgrimage preparation (road conditions, transportation, parking, location accessibility); and religious atmosphere as numinous experience (sacred ambiance, tranquility, religious ornamentation, spiritual atmosphere). Through thematic analysis and phenomenological reduction, the research demonstrates that visitor satisfaction transcends conventional service quality metrics, representing holistic spiritual transformation where pilgrims construct meaning through embodied encounters with the sacred. The findings reveal that 86.6% of satisfaction variance reflects these experiential dimensions, while 13.4% represents the irreducible mystery of individual spiritual journey and divine encounter. This study contributes to religious tourism phenomenology by demonstrating how quantitative satisfaction correlates with qualitative spiritual transformation, offering implications for sustainable sacred site management that honors both visitor spiritual needs and religious authenticity while fostering interfaith dialogue and community development.